Community Empowerment Model for Preventing Child Stunting in Malang Regency - Riniwati, Harsuko; Uyun, Dhia Al-; Wike, Wike; Utaminingsih, Alifiulahtin; Setiawati, Eti; Wahyuni, Lilik; Almira, Nabila Sella; Aulia, Lisa; Ndoen, Daisy Pangalila; Fitriyah, Ikhrotul; Ajizah, Lutfia Wirdatul; Irawati, Ina (Sekolah Pascasarjana Universitas Brawijaya, 2025)
Stunting is a chronic nutritional problem due to a lack of long-term nutritional intake, resulting in impaired growth in children. The government's commitment to reducing stunting rates can be carried out through empowerment programs. The highest level of empowerment is reflected in being able to make decisions. This study aims to analyze the factors influencing decision-making related to the community empowerment development model to prevent stunting in children in Malang Regency. The research method uses Smart/PLS analysis. Respondents are stakeholders related to stunting. The study results show that welfare directly influences decision-making regarding stunting prevention. The community at the research location needs to improve welfare to increase their empowerment in reducing stunting. Awareness of stunting problems is a potent mediator for increasing empowerment through welfare and participation. This study suggests that it is necessary to develop welfare programs and community involvement to increase community empowerment and overcome stunting. Keywords: empowerment, welfare, access, participation, critical awareness and control